Concise Review: Modeling Neurodegenerative Diseases with Human Pluripotent Stem Cell‐Derived Microglia - Haenseler, Walther; Rajendran, Lawrence (Stem cells (Dayton, Ohio), 2019)
Inflammation of the brain and the consequential immunological responses play pivotal roles in neurodegenerative diseases such as Alzheimer's disease, Parkinson's disease, amyotrophic lateral sclerosis, and frontotemporal dementia (FTD). Microglia, the resident macrophage cells of the brain, have also emerged as key players in neuroinflammation. As primary human microglia from living subjects are normally not accessible to researchers, there is a pressing need for an alternative source of authentic human microglia which allows modeling of neurodegeneration in vitro. Several protocols for induced pluripotent stem cell (iPSC)‐derived microglia have recently been developed and provide unlimited access to patient‐derived material. In this present study, we give an overview of iPSC‐derived microglia models in monoculture and coculture systems, their advantages and limitations, and how they have already been used for disease phenotyping. Furthermore, we outline some of the gene engineering tools to generate isogenic controls, the creation of gene knockout iPSC lines, as well as covering reporter cell lines, which could help to elucidate complex cell interaction mechanisms in the microglia/neuron coculture system, for example, microglia‐induced synapse loss. Finally, we deliberate on how said cocultures could aid in personalized drug screening to identify patient‐specific therapies against neurodegeneration. Stem Cells 2019;37:724–730 Modelling of neurological diseases can be done in mono‐cultures for many readouts, but for authentic modelling of neuron‐microglia interactions such as synapse pruning events it is crucial to use co‐cultures.